2018
DOI: 10.1029/2018ja025720
|View full text |Cite
|
Sign up to set email alerts
|

Oscillation of the Ionosphere at Planetary‐Wave Periods

Abstract: F‐region ionospheric oscillations at planetary‐wave (PW) periods (2–20 days) are investigated, with primary focus on those oscillations transmitted to the ionosphere by PW modulation of the vertically propagating tidal spectrum. Tidal effects are isolated by specifically designed numerical experiments performed with the National Center for Atmospheric Research thermosphere‐ionosphere‐electrodynamics general circulation model for October 2009, when familiar PW and tides are present in the model. Longitude versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 64 publications
(96 reference statements)
4
50
0
Order By: Relevance
“…The trans‐equatorial winds are consistent with a solar‐driven summer‐to‐winter circulation, but may also be modified by field‐aligned drifts due to in situ winds associated with the lunar tide that propagates into the upper thermosphere (e.g., Forbes et al, ). At higher latitudes, the situation is reversed, with E × B drifts playing a secondary role to that of field‐aligned drifts (see Forbes et al, , for an analogous situation with solar tides). In particular, as shown in Forbes et al (), the appearance of maxima in one hemisphere and/or the other is dependent on the relative amplitudes of the symmetric and antisymmetric modes of M 2 propagating upward from the lower atmosphere, the latter being produced by interaction between the main symmetric mode characterizing the lunar forcing and the asymmetric mean wind field in the middle atmosphere.…”
Section: Results and Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“…The trans‐equatorial winds are consistent with a solar‐driven summer‐to‐winter circulation, but may also be modified by field‐aligned drifts due to in situ winds associated with the lunar tide that propagates into the upper thermosphere (e.g., Forbes et al, ). At higher latitudes, the situation is reversed, with E × B drifts playing a secondary role to that of field‐aligned drifts (see Forbes et al, , for an analogous situation with solar tides). In particular, as shown in Forbes et al (), the appearance of maxima in one hemisphere and/or the other is dependent on the relative amplitudes of the symmetric and antisymmetric modes of M 2 propagating upward from the lower atmosphere, the latter being produced by interaction between the main symmetric mode characterizing the lunar forcing and the asymmetric mean wind field in the middle atmosphere.…”
Section: Results and Interpretationmentioning
confidence: 99%
“…However, we do note some differences in amplitude between 20 • S and 20 • N, and phases are substantially different between hemispheres at 45 • magnetic latitude during a given analysis interval, or between analysis intervals within a given hemisphere. Such differences are possible signatures of field-aligned neutral winds driving Ne variations, as noted by Stening et al (1999) and Pedatella and Maute (2015) for the lunar tide and Forbes et al (2018) for solar tides.…”
Section: Amplitudesmentioning
confidence: 95%
See 1 more Smart Citation
“…There are several possible mechanisms advanced in the literature through which PW‐induced oscillations reach the ionosphere (see, e.g., Forbes, , and Forbes et al, , and references therein); these mechanisms include (1) direct penetration into the E ‐region wind‐dynamo region where the PWs modulate the electric fields that drive plasma drifts in the F ‐region ionosphere resulting in the modulation of the equatorial ionization anomaly (EIA); (2) modulation of tides in the MLT region that reach the dynamo region and extend into the F region, inducing oscillations in the vertical plasma drifts as well as field‐aligned ion motion; (3) secondary PWs in the dynamo region due to the dissipation of PW‐modulated GWs; and (4) PW‐induced changes in thermospheric composition.…”
Section: Intraseasonal Variabilitymentioning
confidence: 99%
“…If planetary‐scale waves modulate the tides, then direct tidal effects on the F ‐region winds might also account for the observed planetary‐scale oscillations. Using TIME‐GCM with lower boundary forcing (approximately 30‐km altitude) provided by 3‐hourly output from the Modern‐Era Retrospective Analysis for Research and Applications (MERRA) and TIE‐GCM (the Thermoshere‐Ionosphere‐Electrodynamics General Circulation Model) Forbes et al () showed that both are important. This result is consistent with earlier work by England et al (), who showed that in addition to coupling through the E ‐region dynamo, tides couple to the ionosphere through F ‐region winds and changes in thermospheric neutral composition ([O]/[N 2 ]).…”
Section: Intraseasonal Variabilitymentioning
confidence: 99%